Prognostic Impact of Clostridium butyricum MIYAIRI (CBM588) in Combination With Pembrolizumab for Advanced Urothelial Carcinoma: A Retrospective Cohort Study - Junya Arima; Hirofumi Yoshino; Shuichi Tatarano; Akihiko Mitsuke; Yoichi Osako; Takashi Sakaguchi; Ryosuke Matsushita; Satoru Inoguchi; Yasutoshi Yamada; Hideki Enokida (Cancer Reports)
ABSTRACT Background Combining the probiotic product CBM588 with immune checkpoint inhibitors (ICIs) has shown improved prognosis in several cancers. Pembrolizumab alone as a second‐line treatment for urothelial cancer (UC) extends prognosis by only 3 months. Aims This is a retrospective study that examined the effects of CBM588 combined with pembrolizumab in advanced UC. Methods and Results The study included 44 patients who had recurrence or progression after first‐line chemotherapy with cisplatin or carboplatin. The study compared 33 patients treated with pembrolizumab alone and 11 patients treated with CBM588 plus pembrolizumab over a median observation period of 12 months. The combination of CBM588 and pembrolizumab significantly improved progression‐free survival (PFS; p = 0.004) and overall survival (OS; p = 0.02). Multivariate analysis identified CBM588 as a significant prognostic factor for both PFS (hazard ratio: 0.074, p = 0.0008) and OS (hazard ratio: 0.105, p = 0.0056). Conclusion These results suggest the effectiveness of the CBM588 combination with ICI treatment in UC.